PENGARUH KEPUASAN KERJA TERHADAP KINERJA KARYAWAN MELALUI PRESTASI KERJA SEBAGAI VARIABEL INTERVENING PADA BADAN PERTANAHAN NASIONAL (BPN) DI SITUBONDO - Istiqomaria, Eka Yulia; Pramesthi, Riska Ayu; Karnadi, Karnadi (Fakultas Ekonomi dan Bisnis, 2022)
BPN (National Land Agency) is a non-ministerial government Agency in Indonesia which has thetask of carrying out government duties in the land sector in accordance with the provisions of thelegislation. The purpose of this study was to analyze and examine the effect of job satisfaction on employee performance through job performance as an intervening variable (study at the National Land Agency of Situbondo Regency). The sampling technique used was the saturated sampling technique. Data analysis and hypothesis testing in this study used the Structural Equation - PartialLeast Square (PLS-SEM) model. The results of the direct influence hypothesis test using the Smart PLS 3.0 application, indicate that job satisfaction has a significant effect on job performance, job satisfaction has a signifikan effect on performance, job performance has a significant effect on performance. The results of the indirect effect hypothesis test show that the variabel job satisfaction on performance through work commitment has a significant positive effect.